ADS553 - Strategic Management for Public Sector / Faculty of Administrative Science & Policy Studies - UiTM, Faculty of Administrative Science & Policy Studies (Universiti Teknologi MARA (UiTM), 2021)
Strategic management is a set of managerial skills that emphasize throughout the public sector. The purpose is to establish and employ the most suitable strategic option that is best suited to the public sector. Real-life examples and case studies will be used to examine the practice of strategic management and evaluate its impact on the public sector.